Penggunaan Perjanjian Buku dalam Transaksi Bisnis Menurut Hukum Islam - Abdul Karim Munthe (Universitas Islam Negeri Jakarta, 2015)
Contract is the basic point of a transaction, including the transactions in Islamic economic. The rapid development of Islamic economics forcesan adaptation of economic contract in accordance with the development of society. Standard contract is a common form for printing an agreement. It is a contract that has been set unilaterally by the company. Theoretically, standard contract is accepted both in positive law in Indonesia and Islamic law (based on habitual or ‘urf. Standard contract should consider legal protection for both parties, especially consumers. Standard contracts should create justice, equality and prioritize the concept of khiyar.DOI: 10.15408/ajis.v15i2.2865